Anaerobically fermented spent mushroom substrates improve nitrogen removal and lead (II) adsorption - Yunlong Yang (IWA Publishing, 2021)
In this study, spent mushroom substrates (SMSs) were fermented anaerobically at room temperature to gain liquid SMSs (LSMSs) that were used to remove nitrogen from the piggery wastewater with a low C/N ratio in a sequencing batch reactor (SBR) and solid SMSs (SSMSs) that were utilized to adsorb Pb2+ from Pb2+-containing wastewater in a fixed-bed reactor (FBR). After LSMSs supplement, the removal efficiency of both total nitrogen (TN) and NH+4-N increased from around 50% to 60–80%. High-throughput sequencing results presented an obvious change in microbial diversity, and some functional microorganisms like Zoogloea and Hydrogenophaga predominated to promote nitrogen removal. Pb2+ did not emerge from the effluent until 240 min with the corresponding concentration being less than 3 mg/L when using 30-day SSMSs as adsorbents, and it was demonstrated to be appropriate to use the Thomas model to predict Pb2+ sorption on SSMSs. Although various functional groups played a role in binding ions, the carboxyl group was proved to contribute most to Pb2+ adsorption. These results certified that the anaerobically fermented SMSs are decidedly suitable for wastewater treatment. HIGHLIGHTS Anaerobically fermented spent mushroom substrates (AFSMS) could be recycled entirely.; AFSMSs were suitable for the treatment of piggery wastewater with a low C/N.; AFSMSs had a much higher capacity to adsorb Pb2+ than native SMSs.;